Fusarium Head Blight in Barley from Subtropical Southern Brazil: Associated Fusarium Species and Grain Contamination Levels of Deoxynivalenol and Nivalenol - Emanueli Bizarro Furtado; Eduardo Guatimosim; Danielle Ribeiro de Barros; Carlos Augusto Mallmann; Jeronimo Vieira de Araujo Filho; Sabrina de Oliveira Martins; Dauri José Tessmann; Cesar Valmor Rombaldi; Luara Medianeira de Lima Schlösser; Adriana Favaretto; Leandro José Dallagnol (Plants)
Fusarium head blight in barley (Hordeum vulgare) reduces grain yield and can lead to the accumulation of deoxynivalenol (DON) and nivalenol (NIV) in grains. We surveyed Fusarium species and evaluated DON and NIV concentrations in barley grains in four regions of Rio Grande do Sul, the southernmost state in subtropical Brazil. Seven Fusarium species were identified: F. asiaticum, F. avenaceum, F. cortaderiae, F. graminearum, F. gerlachii, F. meridionale and F. poae. DON (0 to 10,200 µg/kg) and NIV (0 to 1630 µg/kg) were detected in 74% and 70% of the samples, respectively, with higher concentrations found in experimental fields. However, in commercial barley fields, most samples fell below 2000 µg/kg of DON, which is the maximum limit allowed by Brazilian legislation for grains intended for processing. The seasonality of temperature and precipitation influenced mycotoxin concentrations. Therefore, the variability of Fusarium species in Rio Grande do Sul and a high incidence of DON and NIV in barley grains highlight the complexity of this pathosystem. This variability of Fusarium species may also influence the effectiveness of measures to control the disease, particularly in relation to genetic resistance and fungicide application.